Auto aggregation activity and antibiotic susceptibility as a potential probiotic properties of lactic acid bacteria (LAB) isolated from Malaysian fermented foods - Siti Nasiroh, Ismail; Nina Suhaity, Azmi; Makky, Essam A. (2017)
Malaysia has a wide variety of fermented foods that beneficial for health. The most commonly studied beneficial microbes of fermented foods are Lactic acid bacteria (LAB). Other than developing of desired flavor and odor of those fermented food, Lactic acid bacteria also has high probiotic potential. However, the probiotic properties of lactic acid bacteria naturally occurring in Malaysian fermented foods still remains unexplored. Therefore, present study aimed on isolation of lactic acid bacteria from Malaysian fermented foods and examination of various phenotypic identification and study characteristics related to the probiotic potential of these microorganisms. Pekasam (fermented fish), jeruk maman (fermented vegetable), tapai (fermented glutinuous rice) and tempoyak (fermented durian) were used as a source of Lactic acid bacteria. Isolated strains were identified their colonies morphologies, physiological and biochemical test to confirm their genus. All strains were matched with characteristics of LAB by showing a negative catalase test, gram positive and rod shaped bacteria. They were mesophilic bacteria and survived at 1.5%, 2.5%, 5%, 7.5% and 10% of NaCl concentration. Further twenty selected strains were determined antibiotic susceptibility to selected eight antibiotics and auto aggregation activity. All the selected strains showed various susceptibilities toward antibiotics. All selected strains showed high auto aggregation percentage after being incubated at room temperature for 24 h. Among the samples used, lactic acid bacteria isolated from pekasam (fermented fish) showed the best probiotic potential with high auto aggregation percentage and resistance to all antibiotics. The availability of lactic acid bacteria isolated from pekasam (fermented fish) had potential application in functional foods and health-associated products. This fermented foods are commercially available and information obtained from this study could contribute to the potential use of these LAB isolates as a probiotic in the food and pharmaceutical industries.